Parallel social network crawler system - Lim, Ivan Wei Jie. (2012)
Crawling social network data can uncover interesting phenomena for a variety of usage. However it is also generally sluggish due to the fact that it requires 3rd party services over a competitive network. These services are provided at their discretion and their usage quota needs to be complied. Therefore, it resulted in the need to accelerate the retrieval process, which is the objective of this project, to exploit parallelism so as to speed up the crawling procedure.